2004
DOI: 10.1097/01.olq.0000137901.71284.6b
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Impact of Testing Individuals with No History of Genital Herpes for Herpes Simplex Virus Type 2

Abstract: There was no apparent lasting adverse psychosocial impact of detecting HSV-2 infection among individuals without a history of genital herpes seeking herpes testing at an STD clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…Concerns range from issues surrounding the accuracy of the tests, to the burden on healthcare practitioners of providing appropriate counseling, to the psychosocial distress that may accompany a new diagnosis of genital herpes [46,47]. Recent studies addressing these concerns have been reassuring: no lasting distress was identified in persons receiving a serologic diagnosis of HSV-2 infection [48][49][50]. Physicians should encourage patients to disclose their genital herpes to partners before the initiation of sexual activity, as currently recommended [8].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns range from issues surrounding the accuracy of the tests, to the burden on healthcare practitioners of providing appropriate counseling, to the psychosocial distress that may accompany a new diagnosis of genital herpes [46,47]. Recent studies addressing these concerns have been reassuring: no lasting distress was identified in persons receiving a serologic diagnosis of HSV-2 infection [48][49][50]. Physicians should encourage patients to disclose their genital herpes to partners before the initiation of sexual activity, as currently recommended [8].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies also compared participants who tested HSV-2 positive with participants who tested HSV-2 negative 25 28 31 32. Three studies compared responses in HSV-2-positive participants with and without a history of genital herpes 27 30 33…”
Section: Resultsmentioning
confidence: 99%
“…Concerns about psychosocial distress in persons who are seropositive for HSV-2 have been diminished by studies showing that the effect is limited and transient [54][55][56]. Pending the outcome of studies that are underway, the use of suppressive acyclovir to decrease HIV-1 transmission or improve the clinical course of the HIV-1 infection may become additional important reasons for early diagnosis of HSV-2 infection in HIV-infected persons.…”
Section: ] Patients Identified As Being Coinfected With Hsv-2 Andmentioning
confidence: 94%